Bimbingan Belajar Ppkn Menggunakan Media Pembelajaran Umum SDN 06 Kampung Bali - Redo Julianto; Elfahmi Lubis; Septina Lisdayanti; Romadhona Kusuma Yudha (Universitas Dehasen Bengkulu, 2023)
Learning media comes from two words, namely media and learning, media literally means intermediary or introduction, while learning is an activity or activities to make someone embarrassed to learn. General learning media for learning PPPKN can be one of the keys to achieving learning goals, students at SDN 06 Kampung Bali can understand better and absorb more information because students can imagine and experience first-hand a replica of something they will learn. Citizenship education is one of the important values ​​that must be introduced to children from an early age and to the general public. This study aims to: (1) Know the conditions of Civics learning and teaching activities prior to the implementation of general-based learning media development. (2). Knowing the development of general-based learning media in SDN 06 Kampung Bali. The use of media in learning can make it easier for students to understand something abstract to be more concrete. The results of his research, that in the first experiment of PPKn tutoring using general learning media at SDN 06 Kampung Bali, using the lecture method there were still many students who had not reached the KKM, namely around 17 out of 32 students. Whereas in the second experiment they still used general learning media, but the teacher was not monotonous, so students could be more active, creative and dare to ask questions. By using this method, 6 out of 32 students did not reach the KKM, so using this method made students dare to ask questions independently and creatively.